2012
DOI: 10.1007/s11481-012-9427-3
|View full text |Cite
|
Sign up to set email alerts
|

Amyloid-β-Induced Astrocytic Phagocytosis is Mediated by CD36, CD47 and RAGE

Abstract: Astrocytes, the most numerous glial cell in the brain, have multiple functions and are key to maintenance of homeostasis in the central nervous system. Microglia are the resident immunocompetent cells in the brain and share several functions with macrophages, including their phagocytic ability. Indeed microglia are the resident phagocytes in the brain and express numerous cell surface proteins which act to enable receptor-mediated phagocytosis. However recent evidence suggests that astrocytes express some gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
84
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(90 citation statements)
references
References 42 publications
4
84
0
2
Order By: Relevance
“…Supporting a phagocytic role for reactive astrocytes in AD, it has been suggested that they could mediate Aβ clearance (Osborn et al, 2016) and limit amyloid deposits (Xiao et al, 2014) since these glial cells express many potential phagocytic receptors that bind Aβ (Jones, Minogue, Connor, & Lynch, 2013; Sokolowski & Mandell, 2011). Moreover, astrocytes in culture are highly phagocytic cells (Roldán, Gogg, Ferrini, Schillaci, & De Nicola, 1997; Tansey & Cammer, 1998), and can phagocytose Aβ (Wyss‐Coray et al, 2003) and apoptotic cells (Chang, Barbaro, & Pieper, 2000) and effectively engulf whole dead cells following neural scratch injury in vitro (Lööv, Hillered, Ebendal, & Erlandsson, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Supporting a phagocytic role for reactive astrocytes in AD, it has been suggested that they could mediate Aβ clearance (Osborn et al, 2016) and limit amyloid deposits (Xiao et al, 2014) since these glial cells express many potential phagocytic receptors that bind Aβ (Jones, Minogue, Connor, & Lynch, 2013; Sokolowski & Mandell, 2011). Moreover, astrocytes in culture are highly phagocytic cells (Roldán, Gogg, Ferrini, Schillaci, & De Nicola, 1997; Tansey & Cammer, 1998), and can phagocytose Aβ (Wyss‐Coray et al, 2003) and apoptotic cells (Chang, Barbaro, & Pieper, 2000) and effectively engulf whole dead cells following neural scratch injury in vitro (Lööv, Hillered, Ebendal, & Erlandsson, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Stimulation of astrocyte pattern recognition receptors by DAMPs results in nuclear-factor-κB (NFκB) signaling, the production of proinflammtory cytokines like tumor necrosis factor α (TNFα), α-chemokines, as well as inflammatory mediators cyclooxygenase-2 and matrix metalloproteinase 9 (MMP-9) (Pedrazzi et al, 2007; Ponath et al, 2007; Gorina et al, 2011). Intriguingly, amyloid-β mediated activation of astrocyte RAGE stimulates astrocytes themselves to become phagocytic and engulf extracellular amyloid-β (Jones et al, 2013), possibly implicating reactive astrocytes in the clearance of neuro- and gliotoxic amyloid protein after injury. Additionally, pathogen-associated molecular patterns (PAMPs) from bacterial pathogens, such as lipopolysaccharide also bind astrocyte pattern recognition receptors and elicit expression of immunomodulatory and pro-inflammatory molecules (Hoarau et al, 2011; Hamby et al, 2012).…”
Section: Reactive Astrocytes Regulate Tbi-associated Inflammationmentioning
confidence: 99%
“…Reactive astrocytes are phagocytic cells that are able to ingest dead cells, neuronal synapses, and protein aggregates of Aβ and α-synuclein [18][19][20][21][22]. Especially in early stages of AD, astrocytes appear to be even more efficient than microglia in engulfing Aβ [22].…”
Section: Introductionmentioning
confidence: 99%